ANALISIS SLOW LEARNER DAN RESPON SISWA PADA PEMBELAJARAN IPAS DI KELAS III SD IT PLUS QURTHUBA - Rian Mansyur; Waddi Fatimah; Syamsul Alam; A.Alfiani Damayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to identify the learning difficulties and responses of slow learner students in IPAS learning in grade III of SD IT Plus Qurthuba. This study employs a qualitative approach using a case study method. Data were collected through interviews and documentation with the IPAS teacher who is also the class homeroom teacher, as well as two slow learner students. The results indicate that slow learner students experience difficulties in understanding scientific terms, tend to forget easily, and often fall behind in their studies. Student responses to IPAS learning improve when teachers utilize visual media and small group learning. Other inhibiting factors include a lack of learning support at home and teaching methods that do not align with students' learning styles. Suggested solutions include the use of varied media, language simplification, formation of small groups, and increased parental involvement. This research is expected to serve as a reference for more inclusive IPAS learning.